2023
DOI: 10.1111/1462-2920.16426
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface composition, released polysaccharides, and ionic strength mediate fast sedimentation in the cyanobacterium Synechococcus elongatusPCC 7942

Abstract: Cyanobacteria are photosynthetic prokaryotes of high ecological and biotechnological relevance that have been cultivated in laboratories around the world for more than 70 years. Prolonged laboratory culturing has led to multiple microevolutionary events and the appearance of a large number of ‘domesticated’ substrains among model cyanobacteria. Despite its widespread occurrence, strain domestication is still largely ignored. In this work we describe Synechococcus elongatus PCC 7942‐KU, a novel domesticated sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…Correlating with the SigF1-dependence of pilA1 gene expression, SigF1-deficient strains were found to easily precipitate at the bottom in liquid culture without agitation (Fig. S5), as is consistent with a recent independent observation (Zedler et al, 2023).…”
Section: Pila1 Operon Transcripts Accumulate Under Illumination Depen...supporting
confidence: 90%
See 1 more Smart Citation
“…Correlating with the SigF1-dependence of pilA1 gene expression, SigF1-deficient strains were found to easily precipitate at the bottom in liquid culture without agitation (Fig. S5), as is consistent with a recent independent observation (Zedler et al, 2023).…”
Section: Pila1 Operon Transcripts Accumulate Under Illumination Depen...supporting
confidence: 90%
“…In this study, we found that the pilA1 gene, encoding type IV pilin, is transcribed by RNA polymerase containing the group 3 sigma factor SigF1 in Synechococcus, which appears to be responsible for the sedimentation phenotype (Zedler et al, 2023).…”
Section: Discussionmentioning
confidence: 77%
“…The T1SS, for example, plays a role in heterocyst development and deposition of the Slayer [13][14][15][16] . And T4P are involved in phototaxis, DNA uptake, aggregation, and flotation [17][18][19][20][21][22] . Interestingly, the recent discovery of multiple protein secretion mechanisms that do not involve the aforementioned systems suggests that there may be a myriad of secreted proteins which remain largely unexplored [23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%